2016
DOI: 10.1002/pon.4200
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of baseline cancer-related cognitive impairment in cancer patients scheduled for a curative treatment

Abstract: Premorbid IQ and fatigue are important predictors of baseline CRCI. Therefore, we advise researchers to implement a short IQ test when conducting clinical trials on CRCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…The American Cancer Society includes in its definition of CRCI problems in the cognitive domains of memory, attention, executive function, and processing speed, although research has also found impairment in working memory, new learning, visuospatial skills, and language . The clinical prevalence of CRCI has primarily been assessed in breast cancer patients and survivors . Longitudinal neuropsychological assessment of breast cancer patients finds that up to 75% of patients experience CRCI during treatment, and up to 35% experience CRCI months or years after completion of treatment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Cancer Society includes in its definition of CRCI problems in the cognitive domains of memory, attention, executive function, and processing speed, although research has also found impairment in working memory, new learning, visuospatial skills, and language . The clinical prevalence of CRCI has primarily been assessed in breast cancer patients and survivors . Longitudinal neuropsychological assessment of breast cancer patients finds that up to 75% of patients experience CRCI during treatment, and up to 35% experience CRCI months or years after completion of treatment .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of delineating the nature of cognitive dysfunction due to cancer treatments and identifying ways to predict, assess, and manage these changes is becoming increasingly emphasized in the literature. However, the majority of studies addressing CRCI utilize samples of young‐to‐middle‐aged female breast cancer patients/survivors . In recent years, researchers have begun examining CRCI in other cancer types, although older adults and males are still not well‐represented in these samples.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in cancer treatments have led to improved survival rates, but adverse effects of diagnosis and treatment can impact quality of life (QoL). Cancer‐related cognitive impairment (CRCI) is frequently reported by patients and has been well documented . Up to 30% of cancer patients experience CRCI before beginning treatment, as many as 75% experience cognitive dysfunction during treatment, and up to 35% experience long‐term CRCI after treatment completion .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer-related cognitive impairment (CRCI) is frequently reported by patients and has been well documented. 1,2 Up to 30% of cancer patients experience CRCI before beginning treatment, as many as 75% experience cognitive dysfunction during treatment, and up to 35% experience long-term CRCI after treatment completion. 1,3 Cancer-related cognitive impairment impacts vary from subtle to pronounced, interim to permanent, and stable to progressive 4 and can involve cognitive domains including memory, attention, processing speed, motor function, and executive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of prospective data, it has been noted that cognitive deficits may be present in a substantial number of patients before adjuvant or neoadjuvant chemotherapy begins (119), implying that the etiology of cognitive dysfunction in this setting may be multifactorial (120). Additionally, endocrine therapy has also been linked to cognitive decline in this setting (121).…”
Section: Introductionmentioning
confidence: 99%